228k views
3 votes
F(x)= -x^2+ 6x -2 convert to vertex form

2 Answers

6 votes

Answer:

f(x) =- (x - 3)² + 7

Explanation:

a parabola in vertex form is

f(x) = a(x - h)² + k

where (h, k ) are the coordinates of the vertex and a is a multiplier

to obtain vertex form use the method of completing the square

add/subtract ( half the coefficient of the x- term )²

f(x) = - x² + 6x - 2 ( factor out - 1 from the first 2 terms )

= - 1 (x² - 6x) - 2

= - (x² + 2(- 3)x + 9 - 9 ) - 2

= - (x - 3)² + 9 - 2

= - (x - 3)² + 7

User Ramen
by
4.6k points
4 votes

Answer:


y=-(x-3)^2+7

Explanation:


f(x)=-x^2+6x-2\\\\y=-x^2+6x-2\\\\y-7=-x^2+6x-2-7\\\\y-7=-x^2+6x-9\\\\y-7=-(x^2-6x+9)\\\\y-7=-(x-3)^2\\\\y=-(x-3)^2+7

User Jaime Febres
by
4.7k points